중소기업 최고경영자(CEO 및 임원)의 커리어 야망과 자기자비가 혁신행동에 미치는 영향에 관한 연구 - 최진숙(Jinsook Choi); 황금주(Kumju Hwang) (벤처창업연구, 2018)
Considering that the subject of innovation of SMEs is the CEO, it is very important to study the innovation behavior of the CEO at the individual level. The purpose of this study is to examine factors affecting innovation work behavior of SME CEOs. The purpose of this study was to examine the effects of self-compassion and self-transcendence on innovation work behavior, which are the emotional intelligence factors that show the psychological growth and potential of individual, and the career ambition and positive psychological capital did. In order to verify the research hypothesis, we analyzed 238 questionnaires collected from CEOs and executives of SMEs focused on auto parts and manufacturing. Factors affecting innovation behavior of SME CEO are summarized as follows. First, career ambition has a positive effect on positive psychological capital. Second, positive psychological capital has a positive effect on innovation work behavior. Third, self-compassion of CEO has positive influence on self - transcendence. Fourth, the self-transcendence of CEO has a positive effect on innovation work behavior. This study confirms the relationship between CEO career ambition, positive psychological capital, self-compassion, self-transcendence, and innovation work behavior of SME CEO and confirms the influence relationship between positive psychological capital and self-transcendence It is meaningful. Finally, theoretical and practical implications were discussed based on the results of the study. 중소기업의 혁신의 주체가 최고 경영자라는 점을 고려할 때 최고 경영자 개인수준의 혁신행동에 대한 연구는 매우 중요하다. 본 연구는 중소기업 최고 경영자의 혁신행동에 영향을 주는 요인을 검증하고자 하였다. 혁신행동의 선행요인으로 최고 경영자의 심리적 특성 중 동기부여 변인인 커리어 야망과 긍정심리자본을 그리고 개인의 심리적 성장과 잠재력 발휘를 나타내는 정서지능 요인인 자기자비와 자기초월이 혁신행동에 미치는 영향을 분석했다. 연구가설을 검증하기 위해서 자동차 부품 및 제조업 중심의 중소기업 CEO와 임원을 대상으로 회수한 설문지 238부를 실증 분석하였다. 중소기업 최고 경영자들의 혁신행동에 영향을 미치는 요인들은 분석한 연구결과를 요약하면 다음과 같다. 첫째, 커리어 야망은 긍정심리자본에 정(+)의 영향을 미쳤으며, 둘째, 긍정심리자본은 혁신행동에 정(+)의 영향을 미쳤다. 셋째, 최고 경영자의 자기자비는 자기초월에 정(+)의 영향을 미쳤으며, 넷째, 최고 경영자의 자기초월은 혁신행동에 정(+)의 영향을 미치는 것으로 나타났다. 본 연구는 중소기업 최고 경영자의 커리어 야망, 긍정심리자본, 자기자비, 자기초월, 혁신행동 간의 영향관계를 확인하였으며, 특히 중소기업 최고 경영자의 긍정심리자본과 자기초월이 혁신행동 간의 영향관계를 확인하였다는데 의의가 있다. 마지막으로 연구결과를 바탕으로 이론적, 실무적 시사점을 논의 하였고, 연구의 한계점 및 향후 연구 방향을 제시하였다.